Driving Employee Sustainable Performance through Environmental Support, Green Training, and Sustainable Leadership: Does Cultural Intelligence Matter? - Zhang, Qianhui (International Review of Management and Marketing, 2026)
This study examines how environmental support, green training, and sustainable leadership relate to employee sustainable performance, with cultural intelligence positioned as a mediating mechanism. The research is conducted in Chinese-foreign cooperative institutions (CFCIs) across multiple provinces in China, where dual governance structures, culturally diverse teams, and cross-national educational practices create a complex organizational setting for sustainability-oriented behavior. Data were collected from 296 academic and administrative employees working in these institutions, and the proposed model was analyzed using SmartPLS. By focusing on multicultural higher education institutions, this study extends sustainability and organizational behavior research into an underexplored context in which both organizational practices and cross-cultural capabilities are likely to shape employee outcomes. The study offers a framework for understanding how supportive environmental conditions, sustainability-focused training, and leadership can foster employee sustainable performance through the development of cultural intelligence. The findings are expected to provide practical insights for managers and policymakers in CFCIs seeking to strengthen sustainable work practices and improve employee effectiveness in culturally diverse institutional environments.